AMPA Receptor-Mediated Ca2+ Transients in Mouse Olfactory Ensheathing Cells - Beiersdorfer, Antonia; Lohr, Christian (Frontiers in Cellular Neuroscience, 2019)
Ca2+ signaling in glial cells is primarily triggered by metabotropic pathways and the subsequent Ca2+ release from internal Ca2+ stores. However, there is upcoming evidence that various ion channels might also initiate Ca2+ rises in glial cells by Ca2+ influx. We investigated AMPA receptor-mediated inward currents and Ca2+ transients in olfactory ensheathing cells (OECs), a specialized glial cell population in the olfactory bulb (OB), using whole-cell voltage-clamp recordings and confocal Ca2+ imaging. By immunohistochemistry we showed immunoreactivity to the AMPA receptor subunits GluA1, GluA2 and GluA4 in OECs, suggesting the presence of AMPA receptors in OECs. Kainate-induced inward currents were mediated exclusively by AMPA receptors, as they were sensitive to the specific AMPA receptor antagonist, GYKI53655. Moreover, kainate-induced inward currents were reduced by the selective Ca2+-permeable AMPA receptor inhibitor, NASPM, suggesting the presence of functional Ca2+-permeable AMPA receptors in OECs. Additionally, kainate application evoked Ca2+ transients in OECs which were abolished in the absence of extracellular Ca2+, indicating that Ca2+ influx via Ca2+-permeable AMPA receptors contribute to kainate-induced Ca2+ transients. However, kainate-induced Ca2+ transients were partly reduced upon Ca2+ store depletion, leading to the conclusion that Ca2+ influx via AMPA receptor channels is essential to trigger Ca2+ transients in OECs, whereas Ca2+ release from internal stores contributes in part to the kainate-evoked Ca2+ response. Endogenous glutamate release by OSN axons initiated Ca2+ transients in OECs, equally mediated by metabotropic receptors (glutamatergic and purinergic) and AMPA receptors, suggesting a prominent role for AMPA receptor mediated Ca2+ signaling in axon-OEC communication.